Removal of Dye Stuff from Industrial Effluents Using MnWO4 as Semiconductor - Surana, Jyoti; Bhardwaj, Shipra (Asian Journal of Chemistry, 2010)
The bleaching of Eosin-Y was carried out in presence of semiconductor MnWO4. The source used for energy was visible light. Various parameters like amount of semiconductor, pH, light intensity, dye concentration, etc. were varied. A tentative mechanism is proposed.